2017
DOI: 10.1002/jee.20183
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Students' Epistemic Cognition in the Context of Problem Solving

Abstract: Background Students' beliefs about knowledge (epistemic beliefs) and their motivations toward processing information (epistemic motivation) have been suggested as influencing aspects of learning. Purpose This study investigated the relationship between engineering students' approach to solving an open‐ended homework problem and their epistemic motivation, engineering epistemic beliefs, and epistemic cognition. Methods The initial quantitative phase of this sequential explanatory mixed methods study employed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 44 publications
0
61
0
Order By: Relevance
“…One publication made use of a methods flowcharts to illustrate their design and where mixing occurred. Faber and Benson's [32] work in the Journal of Engineering Education sought to explore the relationship between the approach an engineering student takes to solving an openended homework problem and different latent constructs: epistemic motivation, engineering epistemic beliefs, and epistemic cognition. They used a sequential explanatory mixed methods study to do so, which can be quickly gleaned from the flowchart in Figure 2.…”
Section: Interpretive Comprehensiveness: Framing Results By Constructmentioning
confidence: 99%
See 3 more Smart Citations
“…One publication made use of a methods flowcharts to illustrate their design and where mixing occurred. Faber and Benson's [32] work in the Journal of Engineering Education sought to explore the relationship between the approach an engineering student takes to solving an openended homework problem and different latent constructs: epistemic motivation, engineering epistemic beliefs, and epistemic cognition. They used a sequential explanatory mixed methods study to do so, which can be quickly gleaned from the flowchart in Figure 2.…”
Section: Interpretive Comprehensiveness: Framing Results By Constructmentioning
confidence: 99%
“…While Shekar et al [50] showed how one could situate their study as a methodological contribution, a component of Faber and Benson [32] we would like to highlight is the idea of 'mixed methods data quality.' Because data analysis is often intertwined with a particular paradigmatic stance or set of assumptions, mixing data together and conducting analyses on the consolidated data carries additional considerations, which is often not acknowledged.…”
Section: Methodological Foundations: Grounding Approaches and Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey with 16 open-ended items pertaining to students' conceptualizations of research and their beliefs about themselves as researchers was developed 13 . This survey also included 45 closed items designed to measure students' engineering epistemic beliefs and need for cognitive closure [14][15][16][17][18][19] , and questions related to participant demographics (self-reported gender, race, ethnicity, year of study, etc.) were placed at the end of the survey.…”
Section: Phase One: Quantitative and Qualitative Data Collection And mentioning
confidence: 99%